Corrosión: inexorabilidad vs. durabilidad - Diaz Tang, Isabel (Pontificia Universidad Católica del Perú, 2016)
In general, a material will tend to corrode in a specific environment when the corrosion products are more stable than the starting material or, when exposed to certain conditions, a corrosion process results favored. In general practice, the goal is to extend the service life of structures, equipment or devices, that is, to improve their durability.

En general, un material tenderá a corroerse espontáneamente en un determinado medio si los productos de corrosión son más estables que el material de partida, o si bajo las condiciones de exposición la corrosión resulta favorecida. En la práctica, lo que se busca es extender la vida útil de estructuras, equipos o dispositivos, es decir, mejorar su durabilidad.
Corrosion: inexorability versus durability
Keywords: Corrosión; Protección contra la corrosión; Furabilidad; https://purl.org/pe-repo/ocde/ford#1.04.00